2023
DOI: 10.3390/nu15102312
|View full text |Cite
|
Sign up to set email alerts
|

Elateriospermum tapos Yoghurt as a Therapeutic Intervention for Obesity-Associated Cognitive Impairments and Anxiety-like Behaviour in a High Fat Diet Maternal Obese Rat Model

Abstract: Maternal obesity can be considered an intergenerational cycle and is also an important indicator of cognitive impairments. It is thought that using natural products is the best and safest way to combat maternal obesity and associated complications. Recent studies have shown that Elateriospermum tapos (E. tapos) contains bioactive compounds with anti-obesity effects, and yoghurt is a convenient medium for supplementing obese maternal rats with E. tapos extract. Thus, the aim of this study is to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The preliminary study has identified that there are 64 bioactive compounds in E. tapos yogurt (Supplementary Table S1) [13,14]. These are the three selected compounds Scropolioside A, Flazin, and Medicagol which have been identified as potential bioactive compounds that fulfill the necessary criteria for drug screening (ADME), as shown in Table 2.…”
Section: Selection Of Potential Bioactive Compoundsmentioning
confidence: 99%
“…The preliminary study has identified that there are 64 bioactive compounds in E. tapos yogurt (Supplementary Table S1) [13,14]. These are the three selected compounds Scropolioside A, Flazin, and Medicagol which have been identified as potential bioactive compounds that fulfill the necessary criteria for drug screening (ADME), as shown in Table 2.…”
Section: Selection Of Potential Bioactive Compoundsmentioning
confidence: 99%